Extrahepatic Manifestations of Hepatitis B Virus Infection: Addison’s Disease and Myelofibrosis in a Patient with Persistent Hepatitis B Surface Antigenemia - François Somlo; Gerald R Berry (Canadian Journal of Infectious Diseases)
A 60-year-old white male patient was admitted to the hospital with acute abdominal pain, seemingly a self-limited ileus. He was found to be hepatitis B surface antigen (HBsAg)-positive. Previous dental treatment was suspected to be the initial source of the infection with hepatitis B virus. Five months later he was re-admitted with a diagnosis of adrenal insufficiency (Addison’s disease) which responded well to steroids. Four years later he developed fever and leucocytosis. A bone marrow biopsy revealed myelofibrosis. He had several episodes of pyrexia during his lifetime. After a 12-year period the patient suffered a fatal myocardial infarction. At autopsy the adrenal glands were reduced to scarred remnants and HBsAg was found to be present in the residual adrenocortical cells by immunoflouresence methods. Bone marrow at autopsy revealed myelosclerosis as well HBsAg (via immunofluoresence). Hepatitis B virus was therefore closely correlated with the development of Addison’s disease and myelofibrosis in this case.